Вплив режимів терморадіаційного нагрівання на ступінь адгезії покриттів при фарбуванні автомобілів - Зубалій, О. В.; Дубовик, В. О.; Zubalii, O.; Dubovyk, V. (ЦНТУ, 2020)
У роботі досліджено вплив режимів термопроменевого нагрівання під час затвердіння лакофарбових матеріалів з порошкових фарб різних кольорів на ступінь адгезії цих покриттів. В результаті раціональні режими затвердіння порошкових фарб різних кольорів були отримані при тепловому випромінюванні нагрівання поверхні зразка. Ці дослідження показують, що ступінь адгезії під час термічного затвердіння суттєво залежить від часу затвердіння. The effect of thermoradiation heating regimes during curing of paint and varnish coatings from powder paints of different colors on the degree of adhesion of these coatings was investigated in the work. As a result, rational modes of curing of powder paints of different colors were obtained by thermoradiation heating of the sample surface. These studies show that the degree of adhesion during thermal radiation curing is significantly influenced by the curing time.
Influence of thermorradiation heating regimes on the degree of coating adhesion when painting cars
Keywords: корозія; адгезія; лакофарбові покриття; порошкові фарби; теплові радіаційні нагрівання; corrosion; adhesion; paint coatings; powder paints; thermal radiation heating